Quantum Computing to Design New More Effective Drugs - Myint, Aung; Hlaing, Nandar; Oo, Zaw Min (Journal of Tecnologia Quantica, 2024)
The development of quantum computing provides great opportunities in various fields, one of which is in drug design. This technology offers a way to model molecular interactions more accurately and efficiently compared to conventional methods. This research aims to explore the potential of quantum computing in designing new drugs that are more effective by accelerating and improving precision in molecular simulations. This study aims to identify and evaluate the ability of quantum computing to design more effective drug compounds, as well as to understand how quantum simulation can improve the efficiency of the drug development process. The research method used is quantum simulation to analyze the interaction between compounds and biological targets. The selected compounds were analyzed using quantum algorithms to calculate bond energy and molecular stability. The results of the simulation are then compared with conventional drug design methods. The results show that quantum computing can model molecular interactions with more precision and efficiency. Compounds selected using quantum methods showed higher effectiveness, with stronger binding energies and more stable biological interactions compared to drug designs using classical methods. Quantum computing shows great potential in the design of new, more effective drugs. Although technical challenges still exist, especially in terms of hardware and algorithms, this research shows that these technologies can speed up and improve the drug design process. Further research is needed to overcome these limitations and optimize the application of quantum computing in the pharmaceutical field.